2006
DOI: 10.1002/ddr.20117
|View full text |Cite
|
Sign up to set email alerts
|

The sunflower seed test: a simple procedure to evaluate forelimb motor dysfunction after brain ischemia

Abstract: We have previously shown that sequential common carotid artery sectioning (SCAS) in mice produces a persistent forelimb flexion. Here, we have extended that study to show that upper limb motor dysfunction after SCAS can be easily quantified with the sunflower seed test. We found that the second artery occlusion significantly increases the time to reach food and that most animals failed or took a longer time to successfully consume the seed with no evidence of recovery (96 h). These alterations were apparently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…Many previous studies have found that CNS lesions can disrupt the movements used in food handling behavior in rodents (e.g., Castro, 1972;Kalil and Schneider, 1975;Kolb et al, 1977;Kolb and Holmes, 1983;Whishaw et al, 1992;Salamone et al, 1993;Whishaw and Coles, 1996;Whishaw et al, 1997;Gomez et al, 2006). The present results are largely consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Many previous studies have found that CNS lesions can disrupt the movements used in food handling behavior in rodents (e.g., Castro, 1972;Kalil and Schneider, 1975;Kolb et al, 1977;Kolb and Holmes, 1983;Whishaw et al, 1992;Salamone et al, 1993;Whishaw and Coles, 1996;Whishaw et al, 1997;Gomez et al, 2006). The present results are largely consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the use of food deprivation, their analysis included stages preparatory to eating (e.g., picking up and flipping the pasta). The time to eat sunflower seeds was increased after cerebral ischemia in mice (Gomez et al, 2006) and after MCAO in rats (Gonzalez and Kolb, 2003), and these studies also used food restriction and included preconsummatory behaviors in the time measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to successfully reach the platform was apparently due to motor impairments in both their limbs: in their hindlimbs during swimming; and in their forelimbs during climbing of the platform. These observations, together with the results of previous studies showing that SCAS produces forelimb flexion with decreased resistance to lateral push and circling behavior, support the idea that in mice, SCAS produces a neurological deficit with hemiparesis or hemiplegia [11,19]. It is clear, however, that other factors, such as fatigue and/or decreased motivation to fulfill the task, that were not explored in this study, could also be involved in the increased time to reach the platform.…”
Section: Discussionsupporting
confidence: 88%
“…Second, following completion of the robbing-and-dodging task, these rats were tested on a task requiring fine motor skills of the forelimbs, which are known to be impaired following mPFC damage (Kolb & Whishaw, 1983; Whishaw et al, 1992). The motor task used was the sunflower seed-husking test, which provides a simple measure for motor disruption in the upper limbs and forepaws (Gomez, Santiago-Mejia, Ventura-Martinez, & Rodriguez, 2006; Whishaw, Sarna, & Pellis, 1998). Briefly, once a rat receives a sunflower seed, it will grasp it with its forepaws and use its digits to manipulate the seed while ripping at the shell with its teeth.…”
mentioning
confidence: 99%